2013
DOI: 10.2527/jas.2013-6283
|View full text |Cite
|
Sign up to set email alerts
|

Survey of transportation procedures, management practices, and health assessment related to quality, quantity, and value for market beef and dairy cows and bulls1

Abstract: This survey consisted of data collected from 23 beef harvest plants to document transportation procedures, management practices, and health assessments of market beef and dairy cows and bulls (about n ≅ 7,000 animals). Gooseneck/bumper-pulled trailers were used more often to transport dairy cattle than beef cattle to market whereas tractor-trailers were used more often to transport beef cattle than dairy cattle. All loads (n = 103) met the American Meat Institute Foundation guidelines for spacing. Loads where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
2
15
0
4
Order By: Relevance
“…Gröhn et al (1998) found that mastitis was the disease that most influenced culling in dairy herds. Studies with data from slaughterhouses reported that between 3% and 9% of dairy culled cows had mastitis, although that may not have been the reported reason for culling (Nicholson et al, 2013). Cows with subclinical mastitis produce less milk and have elevated somatic cell counts (SCC).…”
Section: Risk Factors For Cullingmentioning
confidence: 99%
“…Gröhn et al (1998) found that mastitis was the disease that most influenced culling in dairy herds. Studies with data from slaughterhouses reported that between 3% and 9% of dairy culled cows had mastitis, although that may not have been the reported reason for culling (Nicholson et al, 2013). Cows with subclinical mastitis produce less milk and have elevated somatic cell counts (SCC).…”
Section: Risk Factors For Cullingmentioning
confidence: 99%
“…Numeric scoring of cattle handling is an essential component of many cattle handling and transport assessment programs used to objectively monitor quality of handling (Edge et al, 2005;Grandin, 2010;Nicholson et al, 2013). Numeric scoring of specific cattle handling categories for monitoring welfare in commercial production first gained substantial traction when guidelines were written and subsequently audited routinely in slaughter plants (Grandin, 1997(Grandin, , 2006USDA-FSIS, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors that can affect animal welfare during transport such as temperature, stocking density, and animal condition [43,44,45,46,47]. For sows and boars, research is needed to determine how the animal’s condition before loading interacts with distance travelled, road conditions (smooth vs. rough), temperature, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…The author recommends doing a survey at slaughter plants that processes sows and boars to determine the condition of incoming animals. It should use the same methods as the slaughter surveys that have been conducted for cull dairy and beef cows [44]. Some boars are traveling long distances to a single North American slaughter facility.…”
Section: Discussionmentioning
confidence: 99%